Genomic-based breeding for climate-smart peach varieties - Gogorcena Aoiz, Yolanda; Sanchez, Gerardo; Moreno-Vázquez, Santiago; Pérez, Salvador; Ksouri, Najla (Springer, 2020)
Improving the performance of peach varieties in the context of climate change requires multiple approaches. Not only will climate change alter plant phenology, but it will also drive negative effects of several biotic and abiotic stressors. The challenge is to improve adaptation of varieties to a changing environment, while maintaining organoleptic qualities of the fruit. This chapter focuses on the progress in genomics-assisted breeding in peach to break barriers in conventional breeding. Breeding climate-smart (CS) peach trees requires the identification of CS traits used in the adaptation to high levels of temperature, CO2, water deprivation and biotic stress. Relevant CS traits, such as those that control flowering time (chilling and heat requirements), biotic and abiotic stress tolerance (pests and diseases; water-nutrient efficiency), require prioritization. Here, we review classical mapping and breeding of peach varieties, the progress and limitations of the used of marker-assisted selection and breeding (MAS and MAB, respectively) in expression of traits, such as fruit quality and stress tolerance, and describe the rationale for the use of molecular breeding.